PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, BUDAYA ORGANISASI, DAN KEPUASAN KERJA TERHADAP KUALITAS LAYANAN SEKOLAH PADA KONSENTRASI KEAHLIAN PARIWISATA AKREDITASI A DI SMK KOTA TANGERANG SELATAN - Irine Budi Habsari; Saiful Anwar; Siti Zubaidah (Universitas La Tansa Mashiro, 2025)
This study examines the effects of transformational leadership and organizational culture on job satisfaction and their subsequent impact on school service quality in A-accredited tourism vocational high schools (SMKs) in South Tangerang City. The research employed a quantitative approach with an associative design using a questionnaire survey, involving a population of 247 teachers and a sample of 153 respondents determined through the Slovin formula and proportionate stratified random sampling. Data were analyzed using multiple linear regression and path analysis (trimming model). The findings indicate that transformational leadership, organizational culture, and job satisfaction have positive and significant effects on school service quality, while transformational leadership and organizational culture also have significant positive effects on job satisfaction. These results highlight the importance of strengthening transformational leadership practices and fostering a supportive organizational culture to enhance teachers’ job satisfaction as a pathway to improving school service quality.